Analysis of casing deformation failure mechanism based on fault slip. (September 2021) - Zhang, Xin; Li, Jun; Zhang, Hui; Han, Mengtian; Han, Lihong
Highlights: Fault slip causes casing deformation in shale gas wells. The casing shear strength is obtained through the shear deformation experiment. A three-dimensional finite element model of fault slip is established. Positive correlation between fault slip and casing deformation. Casing deformation prevention methods include reducing displacement, using low elastic modulus cement and small-sized casing. Abstract: Horizontal wells and multi-stage hydraulic fracturing technology make it possible for large-scale commercial exploitation of shale gas. However, the problem of casing deformation of horizontal wells in Sichuan shale gas field has become increasingly prominent, and the Fracturing tools can not be smoothly put to the designed positions. These problems have caused many sections of horizontal wells to be unable to carry out normal fracturing, which has seriously affected the efficient development of shale gas. Field statistics and previous literature studies show that the casing failure mode of Weiyuan shale gas field is shear deformation, and the shear load caused by fault slip is the main factor causing casing deformation. However, the deformation of casing under displacement shear load is still uncertain. The shear deformation experiment of casing is completed, and the strength change law of casing under shear load is obtained. On this basis, the numerical model of wellbore deformation under the action of fault interface slip is established, and the deformation of casing under the action of fault slip and related influencing factors are analyzed. The casing shear test and numerical simulation results are consistent. The results show that there is a linear positive correlation between formation slip and casing deformation. The fault angle, that is, the angle between the fault plane and the wellbore, has a great influence on the deformation of the casing. When the angle is 90°, the casing deformation is the largest. Reducing the elastic modulus of cementing cement stone is beneficial to reduce the casing deformation. The research results can lay a theoretical foundation for the prevention and control of shale gas well casing deformation.